Analysis of Polymeric Immunoglobulin Receptor Expression in Olive Flounder (Paralichthys olivaceus) against Viral Hemorrhagic Septicemia Virus - Kim, Kyung-Hee; Park, Sulhye; Park, Jong-Won; Jeong, Minhwan; Kim, Julan; Kim, Hyejin; Lee, Jeong-Ho; Lee, Dain (Balsaeng'gwa saengsig, 2023)
Polymeric immunoglobulin receptor (pIgR) mediates the transfer of polymeric immunoglobulin to protect organisms and is one of the most important mucosal effectors. In this study, the developmental stage- and tissue-specific expression of pIgR were observed before virus inoculation in olive flounder. pIgR was gradually expressed until the formation of immune tissue, exhibiting high expression in the late juvenile period; thereafter, pIgR expression gradually decreased and exhibited high expression in the spleen and skin. Moreover, pIgR expression after viral hemorrhagic septicemia virus infection was high in the kidney and spleen tissues at high density and low at low density. The results of this study can provide a basis for future studies on breeding density, virus expression, and immune system studies in fish.